Long-term analysis of air temperature trends in Central Asia - Giese, Ernst; Mossig, Ivo; Rybski, Diego; Bunde, Armin (ERDKUNDE, 2007)
Different phenomena, as the enhanced shrinking of glaciers in the Tien Shan and Pamiro Alay, indicate that a climate warming has occurred in Central Asia in the recent past. Thus the questions are since when the climate warming has been taking place and what its intensity has been. A question, which is especially investigated, is whether climate warming in the recent past expresses a trend-like or cyclic development of annual temperature averages. For this purpose analyses of long time series were performed, consisting of monthly and annual air temperature averages at selected climate stations representing typical locations in Central Asia. Applied were methods of the Regression and Correlation Analysis, in particular the Detrended Fluctuation Analysis (DFA), in order to identify long-term correlations and trends in the time series. For the purpose of quantification of occurring trends, the DFA was further extended.